Latent Class Analysis of the cardiometabolic risk factors in children and adolescents: the CASPIAN-V study - Abbas Abbasi-Ghahramanloo; Ramin Heshmat; Amir-masood Rafiemanzelat; Kimia Ghaderi; Mohammad Esmaeil Motlagh; Zeinab Ahadi; Gita Shafiee; Armita Mahdavi-Gorabi; Mostafa Qorbani; Roya Kelishadi (Caspian Journal of Internal Medicine, 2020)
Background: Cardio-metabolic syndrome indicates the clustering of several risk factors. The aims of this study were to identify the subgroups of the Iranian children and adolescents on the basis of the components of the cardio-metabolic syndrome and assess the role of demographic characteristics, socioeconomic status and life style related behaviors on the membership of participants in each latent class. Methods:  This cross sectional study was performed on 3730 Iranian students in 2015 using stratified cluster. All students in each class completed anonymous and structured questionnaires. Abdominal obesity, high triglyceride (TG), low high-density lipoprotein (HDL), high blood pressure (BP), high fasting blood sugar (FBS), high low-density lipoprotein (LDL), high cholesterol and obesity were used for assessing pattern of cardio metabolic risk as a latent variable. Data analysis was performed using PROC LCA in SAS software. Results: Four latent classes were identified in this study; namely 1) healthy (59.6%), 2) low risk (20.4%), 3) moderate risk (13.7%) and 4) high risk (6.4%). Being girl (OR=0.59, 95% CI: 0.46-0.74), living in rural area (OR=0.45, 95% CI;0.33-0.60), high screen time (OR=1.56, 95% CI:1.09-2.24), and parental obesity (OR=1.52, 95% CI: 1.18-1.95) were associated with moderate risk class. Only living in rural area (OR=0.71, 95% CI; 0.51-0.99) was associated with high risk class. Conclusion: About 20% of the students are in the moderate risk and high risk classes.  Design and implementation of interventions according to risk-based class seems necessary with considering probably risk and protective factors for prevention of complications of cardiometabolic syndrome.